Unravelling urban stratigraphy. The study of Brussels’ (Belgium) Dark Earth. An archaeopedological perspective - Devos, Yannick; Vrydaghs, Luc; Degraeve, Ann; Modrie, Sylvianne (Medieval and Modern Matters, 2011)
Abstract Although thick, dark, humic, macroscopically homogeneous units, also known as Dark Earth, are an important part of the urban stratigraphy, their understanding often remains problematic. The aim of the present paper is to demonstrate how archaeopedology contributes to the study of such urban Dark Earth units. Through the example of Brussels’ Dark Earth, we demonstrate that their formation results from multiphased processes whereby various human actions interact with natural phenomena. The formation and transformation of Dark Earth can be understood as an ongoing process of accumulation, erosion, decomposition, homogenisation and other types of soil development that mainly stops once the Dark Earth gets sealed. Among the human activities crop cultivation, gardening, pasture, middening and quarrying have been identified. Main natural phenomena seem to be bioturbation, erosion, alluviation and colluviation. Taking into account that Dark Earth has a polygenetic history, it can be concluded that it should be investigated on a case-by-case basis. Its systematic study enhances our knowledge of the diversity of human and natural events that took place in medieval Brussels, and as such contributes to the understanding of the urban development.